2009
DOI: 10.1007/s00464-009-0433-3
|View full text |Cite
|
Sign up to set email alerts
|

Combination of water-jet dissection and needle-knife as a hybrid knife simplifies endoscopic submucosal dissection

Abstract: The combination of a needle-knife with high-pressure water-jet dissection improved the results of endoscopic submucosal dissection in this experimental setting. Because the frequency of complications is still high, further improvements to the instrument are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 19 publications
0
24
0
2
Order By: Relevance
“…The feasibility of this new device and technology has been tested in the porcine model. Lingenfelder et al 13 reported that the use of HybridKnife with water-jet function shortened the procedure time and injury to the MP. Subsequent studies on the colon and esophagus in porcine models were reported.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The feasibility of this new device and technology has been tested in the porcine model. Lingenfelder et al 13 reported that the use of HybridKnife with water-jet function shortened the procedure time and injury to the MP. Subsequent studies on the colon and esophagus in porcine models were reported.…”
Section: Discussionmentioning
confidence: 98%
“…11 A new system, the HybridKnife, combines electrosurgical technology with a novel water-jet system (ERBEJET 2; ERBE, Tübingen, Germany) that allows rapid needle-free infusion of saline solution in the submucosa to lift a target mucosal lesion. 12,13 Marking, injection, mucosal incision, submucosal dissection, and quite often hemostasis can be performed with this one instrument. This new ESD device may increase the safety of ESD and shorten the procedure time compared with conventional ESD (C-ESD).…”
mentioning
confidence: 99%
“…A new injection device has been introduced, which uses a high-pressure fluid jet though an open tip catheter sans needle that drives the injection solution through the mucosa into the submucosa, creating a fluid cushion similar to that produced by a needle injector. This has been combined with an integral cutting tip (through which the stream is directed) to provide one device that can provide more than a single function [7][8][9]. Fluid that may be injected for polypectomy is often saline, and some endoscopists add a few drops of methylene blue to the injection solution to add color, which may assist in visualization of the edges of the adenoma, which will appear as pink tissue on a bed of blue fluid, rendering easier visualization of the polyp edge.…”
Section: Fluid Injection For Polypectomymentioning
confidence: 99%
“…For several years, our group has focused on the effect of a high-pressure water jet application on the gastrointestinal wall [8][9][10][11]. The water jet dissector has been used successfully for the dissection of parenchymatous organs, mainly the liver, by exploiting the water jet's tissue selectivity [12][13][14][15].…”
mentioning
confidence: 99%